(untitled) (Comparative & International Education Series, 2021)
This chapter sheds light on the history of Historically Black Colleges and Universities (HBCUs). It traces and highlights important hallmarks that make these institutions particularly significant to the African American community. Hallmarks of special importance discussed include the Civil Rights Acts of 1965 and Morrill Act. The chapter further elucidates in detail why HBCUs continue to occupy a significant place in American education landscape. Internationalization as a concept is highlighted within the context of the Civil and Morrill Acts.